2008
DOI: 10.1099/mic.0.2008/020495-0
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the endemic gourmet mushroom Thelephora ganbajun from south-western China

Abstract: The ectomycorrhizal fungus Thelephora ganbajun is an endemic gourmet mushroom in Yunnan province, south-western China. However, despite its widespread consumer appeal, nutritional value and potential ecological role in natural forests, very little is known about its genetics, diversity and ecology. In this study, we investigated DNA sequence variation at the internal transcribed spacer (ITS) regions among 156 specimens collected from 23 sites of nine regions in Yunnan Province. Our analysis identified a total … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 20 publications
4
22
0
Order By: Relevance
“…As DNA barcode sequences increase, barcode-based species identification is becoming increasingly common and the barcode sequences are generating many new species hypotheses. For example, ITS sequences helped reveal divergent lineages within the commercially important wild edible mushrooms Thelephora ganbajun (Sha et al 2008), Russula vinosa , and Boletus (Feng et al 2012). Similar findings have been reported for other organisms such as the root-knot nematodes where DNA barcoding information at four loci identified limitations in species identification based on a single barcode and the usefulness of multiple loci in revealing several new lineages within quarantine root-knot nematodes (Meloidogyne spp.)…”
Section: A Unified and Up-to-date Databasesupporting
confidence: 58%
“…As DNA barcode sequences increase, barcode-based species identification is becoming increasingly common and the barcode sequences are generating many new species hypotheses. For example, ITS sequences helped reveal divergent lineages within the commercially important wild edible mushrooms Thelephora ganbajun (Sha et al 2008), Russula vinosa , and Boletus (Feng et al 2012). Similar findings have been reported for other organisms such as the root-knot nematodes where DNA barcoding information at four loci identified limitations in species identification based on a single barcode and the usefulness of multiple loci in revealing several new lineages within quarantine root-knot nematodes (Meloidogyne spp.)…”
Section: A Unified and Up-to-date Databasesupporting
confidence: 58%
“…These samples included 134 isolates previously analyzed in the Sha et al . 17 study and 242 new isolates collected from 2008–2012. Our samples were obtained from two sources, our own field collections from public lands and local mushroom hunters.…”
Section: Methodsmentioning
confidence: 99%
“…The species is economically very important for the locals and has been heavily harvested to meet both local and regional needs as a food delicacy. A previous study showed abundant sequence variations at the inter-transcribed spacer (ITS) regions of the nuclear ribosomal RNA gene cluster, both within and among local populations of this mushroom 17 . The abundant genetic variations, coupled with the availability of a large number of samples from a relatively small geographic area suggest that this mushroom may represent an excellent system from which to examine the potential for mitochondrial genetic variations in nature.…”
Section: Introductionmentioning
confidence: 96%
“…The mushroom Thelephora ganbajun , known as ‘‘Gan-Ba-Jun’’ in Chinese, is an ectomycorrhizal fungus that grows in symbiosis with pine trees in Yunnan Province of China [7,8,9]. It is a delicious and popular food for its unique flavor.…”
Section: Introductionmentioning
confidence: 99%